A Non-Linear Osteometric Modeling Method for Three-Dimensional Mandibular Morphological Changes During Growth: One-Year Monitoring of Miniature Pigs Using Cone-Beam Computed Tomography - Lin, Hsien-Shu; Lu, Tung-Wu; Li, Jia-Da; Lee, Pei-An; Chen, Yunn-Jy (Frontiers in Bioengineering and Biotechnology, 2022)
Knowledge of mandibular growth and development is essential for diagnosis of malformation and early interception. A previous method of quantifying mandibular growth using the distances between selected anatomical landmarks over the growth period does not provide a complete, quantitative description of the continuous growth patterns. The current study aimed to bridge the gap by measuring the 3D continuous growth of the mandible in miniature pigs using cone-beam computerized tomography (CBCT). The mandibles of the pigs were CBCT-scanned monthly over 12 months, and the 3D mandibular models were reconstructed. A new non-linear, time-dependent osteometric modeling approach was developed to register two consecutive mandible models by searching for the corresponding points with the highest likelihood of matching the anatomical and morphological features so that the morphological changes patterns for each month could be described using color maps on the models. The morphological changes of the mandible were found to decrease anteriorly, with the condyle region and the posterior part of the ramus growing faster than the rest of the mandible. The condyle region showed the fastest growth rate and the posterior ramus the second during the growth period, while the middle and anterior corpus regions showed the slowest growth rates. In conclusion, the current results revealed the non-linear patterns and rates of morphological changes in different growth regions and the whole mandible. The new approach may also be useful for future studies on the growth of the mandible in other animals.